Protease: Serpin complexes to assess contact system and intrinsic pathway activation - Michael W. Henderson; Denis F. Noubouossie; Anton Ilich; Kathy J. Wilson; Rafal Pawlinski; Dougald M. Monroe; Nigel S. Key (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract Mounting evidence suggests that a variety of disease states are pathophysiologically related to activation of the contact system in vivo. The plasma contact system is composed of a cascade of serine proteases initiated by surface activation of factor XII, which can then proceed through a procoagulant pathway by activating the intrinsic coagulation factor XI, or a proinflammatory pathway by activating prekallikrein. Serpins are the primary endogenous inhibitors of the contact system, which irreversibly inhibit their respective protease(s), forming a stable complex. We modified an existing assay strategy for detecting these complexes in plasma using ELISAs and determined the effect of preanalytical variation caused by anticoagulant selection and processing time. The assays were sensitive and specific to inherited deficiency of individual contact factors. We conclude that these assays are robust and represent a relatively simple approach to the assessment of contact factor activation in plasma samples.